Teacher Mentoring: Definitions, Expectations and Experiences from International EFL Teachers - Aydin, Dogus; Arslan, Sezen (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This study aims to investigate pre- and in-service EFL teachers' definitions, expectations, and experiences concerning teacher mentoring. The study sample included EFL teachers from 41 countries: 49 pre-service and 187 in-service EFL teachers teaching at various levels from kindergarten to university. A qualitative research design was employed throughout the study. Data were collected via a questionnaire-based survey and semi-structured interviews. For the analysis of this qualitative data, an in-depth thematic analysis was conducted. Overall, the findings suggest that most of the participants found their mentoring experiences positive. In addition, the participants defined teacher mentoring as a master-apprentice relationship, problem-solving, assisting teachers, and collaboration among them. The study also points out that teachers have different expectations about the necessary knowledge, skills, and attitudes from teacher mentoring. The study's findings have important implications for teacher mentors in EFL teacher training. Implications include, among others, that designing teacher mentoring based on context and needs instead of a master apprenticeship would promote their professional development. Apart from that, the active participation of the stakeholders, such as school directors, would better facilitate the teacher-mentoring process.